Multiscale Paradigms in Integrated Computational Materials Science and Engineering Materials Theory, Modeling, and Simulation for Predictive Design - Deymier, Pierre; Runge, Keith; Muralidharan, Krishna (Springer Series in Materials Science, 2016)
This book presents cutting-edge concepts, paradigms, and research highlights in the field of computational materials science and engineering, and provides a fresh, up-to-date perspective on solving present and future materials challenges. The chapters are written by not only pioneers in the fields of computational materials chemistry and materials science, but also experts in multi-scale modeling and simulation as applied to materials engineering. Pedagogical introductions to the different topics and continuity between the chapters are provided to ensure the appeal to a broad audience and to address the applicability of integrated computational materials science and engineering for solving real-world problems.